2013
DOI: 10.4314/ahs.v13i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Probe substrate and enzyme source-dependent inhibition of UDP-glucuronosyltransferase (UGT) 1A9 by wogonin

Abstract: Background: Drug-metabolizing enzymes (DMEs) inhibition based drug-drug interaction and herb-drug interaction severely challenge the R&D process of drugs or herbal ingredients. Objective: To evaluate the inhibition potential of wogonin (an important flavonoid isolated from the root of Scutellaria baicalensis) towards one of the most important phase II DMEs, UDP-glucuronosyltransferase (UGT) 1A9. Methods: Both recombinant UGT1A9-catalyzed 4-methylumbelliferone (4-MU) glucuronidation reaction and human liver mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The contribution of the different UGT isoforms to drug metabolism is highly variable due to different substrate specificity and different expression levels in organs. Generally, glucuronidation studies of a compound are divided into several aspects [33], including UGT-isoform-specific metabolic fingerprint (GSMF) [34], enzyme kinetics and the evaluation of the importance of glucuronidation in the metabolism of the compounds. Previous studies showed that GL-V9 underwent an extensive metabolism in liver after administration, where it could be catalyzed by a family of UGT [35].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the different UGT isoforms to drug metabolism is highly variable due to different substrate specificity and different expression levels in organs. Generally, glucuronidation studies of a compound are divided into several aspects [33], including UGT-isoform-specific metabolic fingerprint (GSMF) [34], enzyme kinetics and the evaluation of the importance of glucuronidation in the metabolism of the compounds. Previous studies showed that GL-V9 underwent an extensive metabolism in liver after administration, where it could be catalyzed by a family of UGT [35].…”
Section: Introductionmentioning
confidence: 99%
“…According to the chromatogram of 4-MU, a nonselective substrate of UGT2B7, with different concentration gradients (0-1 mM), the standard curve of 4-MU under 316 nm irradiation in C18 HPLC column (4.6 × 250 mm, 5 µm, GL Science, Fukushima, Japan) at a flow rate of 1 mL/min was obtained [30][31][32][33][34][35]. Rutin, nicotifiorin, isovitexin, vitexin, HPAA, DHPAA, aucubin, and asperuloside were dissolved in DMSO.…”
Section: Hplc Assessment Of Inhibitory Effects Of Flavones Against Hu...mentioning
confidence: 99%
“…4-methylumbelliferone (4-MU) has been widely used as a non-specific substrate of UGT to determine the effect of chemicals on UGT activity [30][31][32][33][34][35]. Catalyzed by UGT, 4-MU obtains the glucuronic acid group transferred from UDPGA through a glucuronidation binding reaction.…”
Section: Introductionmentioning
confidence: 99%